(3CfLjd dhbG hGfLjd eQbU hjhMfGs
(3ChdgG (B:s
(3Chd GdehLhO efg ef ChGNQ EfLjd dhbG Hbhdg (B: (3bGdhG dg dbjUQ aCLGHge jShY hbGd dge hOhG eG cGf dbjUQ Edi bjUQ s
(3BNQgG (B:s
(3BNQ GdehLhO efg CKfGA GdHGH GdQGHY YTQ hGdCNjQ ef EfLjd jhMfG ai cdGe HHdGW ddjghO Yf GdeSjM hai bJd jShY hPafg hbjGeg Yf bHQg hXghQg dJdGejPg HYO bjGeJg s
(3LRA efgs
(3fSNI Ydi hQb ZRGd ecJhHI HGdShGcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdcJH GdSeGhjIs